2018
DOI: 10.1177/1534735418766416
|View full text |Cite
|
Sign up to set email alerts
|

Bursera copallifera Extracts Have Cytotoxic and Migration-Inhibitory Effects in Breast Cancer Cell Lines

Abstract: Plants from the Bursera genus are widely distributed in the tropical dry forests of Mexico. In traditional medicine, extracts from different species of Bursera have been used for a wide range of biological activities, including the treatment of cancer-related symptoms. Compounds present in the Bursera genus include lignans, flavonoids, steroids, short-chain aliphatic alkanes, acetates, alcohols, ketones, and terpenoids. In some instances, secondary metabolites of these classes of compounds may induce cytotoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Therefore, the present findings found that TAM/RES–LbL-LCNPs induced cell death in MCF-7 and CAL-51 cells via apoptosis. Therefore, a combinatory treatment with natural products such as flavonoids, alkaloids, polyphenols, and targeted therapy to augment the anti-cancer effect of conventional drugs represents a vital strategy to circumvent TNBC drug resistance against lines such as CAL-51 and MDA-MB-231 [ 73 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the present findings found that TAM/RES–LbL-LCNPs induced cell death in MCF-7 and CAL-51 cells via apoptosis. Therefore, a combinatory treatment with natural products such as flavonoids, alkaloids, polyphenols, and targeted therapy to augment the anti-cancer effect of conventional drugs represents a vital strategy to circumvent TNBC drug resistance against lines such as CAL-51 and MDA-MB-231 [ 73 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a more recent study, the cytotoxic effect of the MeOH extracts obtained from two different populations of leaves of B. copallifera against two breast cancer cell lines MCF7 and MDA-MB-231 (triple negative) was demonstrated, as well as the inhibition of cell migration in the MDA-MB-231 cell line. In this study, hydroxycinnamic acid and flavonols were identified as the main components of the methanolic extract by HPLC-DAD-ESI-MSn analysis [15]. However, the metabolites responsible of these activities are still unknown.…”
Section: Introductionmentioning
confidence: 92%
“…The half-maximal lethal concentration (LC 50 ) was calculated by plotting the extract concentrations against the percentage of damaged cells. The percentage of cell death for both cell lines was calculated by normalizing the absorbance of untreated cells to 100% and considering published reports where the cytotoxicity of extracts has been assessed [58].…”
Section: Cytotoxicity Assaymentioning
confidence: 99%